Jurisprudential Renewal In The Riba-Al-Fadl In Impure Goods - Israr Khan (jihat-ul-islam, 2021)
There are two different opinions regarding Riba-Al-Fadl. The first one allows it and the second one prohibits it. This paper also prohibits it. But it describes that if the contract occurs between pure and impure goods, the impure goods will be sold first and then the pure goods will be bought with this money acting upon on the hadith of the Prophet - peace be upon him.